Yaw control of a flying-wing unmanned aerial vehicle based on reverse jet control. (May 2020) - Zhu, Jiachen; Shi, Zhiwei; Sun, Quanbing; Chen, Jie; Dong, Yizhang; Fu, Junquan
Due to its layout, there are difficulties in realizing heading attitude control of a flying-wing unmanned aerial vehicle. In this paper, a reverse jet control scheme has been designed: (1) to replace the resistance rudders that are used for the yaw control of a conventional flying-wing unmanned aerial vehicle, (2) to assist and optimize heading attitude control, eliminate the adverse effects of the control surface and enhance stealth performance, and (3) to promote the use of rudderless flight for flying-wing unmanned aerial vehicles. To explore the control mechanism and the flow field of the reverse jet scheme, three-dimensional numerical simulations and low-speed wind tunnel experiments were carried out. First, the numerical simulations evaluated the feasibility and effectiveness of the reverse jet control scheme and explored and optimized the excitation parameters for the scheme. Then the forces were measured in a wind tunnel, and particle image velocimetry experiments were carried out. A reverse jet actuator was independently designed to verify the results of the numerical simulation. The results show that when the reverse jet excitation is applied, the jet obstructs the mainstream, destroys the flow field at the excitation position, and causes early separation of the flow, which increases the pressure drag on the wings and produces a control effect. The control effect mainly depends on the separation degree of the leeward surface. The larger the jet momentum coefficient is, the smaller the jet angle is, and the closer the excitation position is to the leading edge, the greater the separation degree of the leeward surface is, the better the heading attitude control effect is.